The effect of hedonic shopping motivation and e-WOM on impulse buying mediated by positive emotion among Sociolla consumers in Jabodetabek area - Veronica Cynthia Welhenly; Liem Bambang Sugiyanto (Journal of Economics and Business Letters, 2026)
This study reveals that positive emotions triggered by hedged shopping motives and digital buzz from eWOM significantly boost shoppers' urge for spur-of-the-moment purchases at Sociolla. Using SmartPLS-driven Structural Equation Modeling (SEM), the analysis of survey data on active Sociolla users uncovers direct and indirect links: hedonic drives and eWOM both spark positive feelings and directly fuel impulse buys, while positive emotions fully bridge the path from these drivers to uncontrolled spending. To quantitatively probe this dynamic, the study surveyed Sociolla's regular customers using structured questionnaires. Ultimately, it highlights how digital chatter and pleasure-seeking impulses cultivate feel-good states that propel snap buying decisions. The limitation of this study lies in the sampling process, which only focuses on Sociolla consumers in the Jabodetabek area. Practically, this research provides implications for Sociolla and other digital beauty industry players to strengthen enjoyable shopping experiences and improve the quality of electronic word-of-mouth (eWOM) through authentic consumer review. Theoretically, this study enriches the consumer behavior literature by validating the mediating function of positive emotions. It connects hedonic motivation and digital information exposure to impulse buying in the beauty e-commerce ecosystem.